2008
DOI: 10.1002/chem.200701333
|View full text |Cite
|
Sign up to set email alerts
|

A General Method for Constructing Optically Active Supramolecular Assemblies from Intrinsically Achiral Water‐Insoluble Free‐Base Porphyrins

Abstract: We have developed a general method to construct optically active porphyrin supramolecular assemblies by using a simple air-water interfacial assembly process. The method involved the in situ diprotonation of the free-base porphyrins at the air-water interface and subsequent assembly under compression. We showed that two intrinsically achiral water-insoluble free-base porphyrin derivatives, 2,3,7,8,12,13,17,18-octaethyl-21H,23H-porphine (H(2)OEP) and 5,10,15,20-tetra-p-tolyl-21H,23H-porphine (H(2)TPPMe), could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 85 publications
4
77
0
Order By: Relevance
“…24 On the other hand, as shown in Fig. S4 (ESI †), the UV-Vis spectra of our present assemblies are also similar to those of the corresponding samples formulated by the traditional bilateral compression geometry.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…24 On the other hand, as shown in Fig. S4 (ESI †), the UV-Vis spectra of our present assemblies are also similar to those of the corresponding samples formulated by the traditional bilateral compression geometry.…”
Section: Resultssupporting
confidence: 66%
“…S4 (ESI †), the UV-Vis spectra of our present assemblies are also similar to those of the corresponding samples formulated by the traditional bilateral compression geometry. 24 These results indicate that the chiroptical signals of our present samples are attributed to the molecular packing of the assemblies. 24 Moreover, it has been suggested that the authenticity of the observed macroscopic chirality through the CD measurement could not be exclusively determined for the solid state samples or for a stirring system, because the detected CD spectra are often contaminated by the LD artifact, which usually originate from the macroscopic anisotropies of a sample.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…With respect to one-dimensional chiral nanostructures, great advances have been achieved in the past few years. However, building chiral nano-/micrometer-sized materials with interesting properties from an achiral molecule [30,31] is of great difficulty. In our report, we studied the self-assembly of organic molecule of thioxanthone-anthracene (TX-A) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the chirality could either be exhibited within molecular level or be shown in the level of supramolecular assemblies [8]. However, the constructions of chiral porphyrin assemblies from achiral porphyrins are always extremely challenging, and were only carried out in a few particular cases [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%